A cobalt oxide carbon nitride composite material containing cationic vacancies and its preparation method and application

By designing a cobalt oxide carbon nitride composite containing cationic vacancies, the problem of insufficient activity of conventional Co3O4 catalysts is solved, efficient PMS activation and organic pollutant degradation are achieved, and good universality and anti-interference properties are achieved.

CN119158613BActive Publication Date: 2025-02-14SHANTOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411668774.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

In the prior art, conventional Co3O4 catalysts have insufficient catalytic activity, and the number of reactive oxygen species produced is limited, which cannot meet the actual requirements for wastewater treatment. At the same time, free radicals are prone to react with inorganic anions and organic matters, reducing the degradation efficiency of target pollutants.

Method used

By designing a cobalt oxide carbon nitride composite material containing cationic vacancies, using carbon nitride nanosheets as a carrier to form a strong metal-support interaction with glycerol-cobalt, it induces abundant cobalt ion vacancies to form Co3-xO4 /CN composite catalyst.

Benefits of technology

The catalyst exhibits good PMS activation and utilization efficiency and p-nitrophenol degradation performance, has good universality and anti-interference properties, and has good reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119158613B_ABST
    Figure CN119158613B_ABST
Patent Text Reader

Abstract

The present invention relates to a cobalt oxide carbon nitride composite material containing cation vacancies and a preparation method and application thereof. The present invention selects an ultrathin carbon nitride nanosheet with a large specific surface area as a carrier, and uses glycerol cobalt with Co-O-Co-O as a periodic skeleton unit as a precursor, combines it with the carbon nitride nanosheet, and then undergoes thermal oxidation treatment to form a Co with cobalt cation vacancies. 3‑x O4 / CN composite catalyst. During the preparation process, the strong metal-support interaction can induce the formation of abundant cobalt ion vacancies and inhibit the agglomeration of oxide nanoparticles, thus achieving Co 3‑x High dispersion of O4. 3‑x The O4 / CN composite catalyst exhibits good PMS activation and utilization efficiency and p-nitrophenol degradation performance. The degradation process does not require light addition. At the same time, the catalyst exhibits good universality and anti-interference for different pollutants and different water environments, and has good reusability. It can be used for PMS activation and degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic pollutant treatment, and specifically relates to a cobalt oxide carbon nitride composite material containing cationic vacancies, and a preparation method and application thereof. Background Art

[0002] Organic pollutants have become one of the main sources of global water pollution, posing a serious threat to the ecological environment and human health. Therefore, the development of efficient and sustainable treatment methods has become a key task in addressing water pollution problems. Advanced oxidation technology has the advantages of strong oxidation ability, fast reaction rate, wide application range, and relatively simple operation, so it shows broad application prospects in wastewater treatment. As an important branch of advanced oxidation technology, the Fenton-like process based on peroxymonosulfate (PMS, an oxidant) has received widespread attention. The development of high-performance PMS activation catalysts that can effectively produce a large number of active oxygen species is the key to improving the efficiency of PMS-based Fenton-like technology.

[0003] Transition metal oxides and their derivatives show high potential in activating PMS due to their good catalytic activity, high abundance, low cost and other advantages. Among many transition metals, cobalt-based oxides (such as Co3O4) have the best PMS activation performance. However, conventional Co3O4 still faces insufficient catalytic activity and the number of active oxygen species produced is limited, which cannot meet the requirements of actual wastewater treatment. Moreover, free radicals dominate the active substances produced by activated PMS, and free radicals easily react with coexisting inorganic anions and natural organic matter, which greatly consumes the number of free radicals and thus reduces the degradation of target pollutants. Recent studies have reported that non-radical pathways, such as 1 It has high selectivity for O2 and high-valent metals (Co(Ⅳ)=O), and has high resistance to interference from inorganic anions. 1 O2 or high-valent metal PMS-activated cobalt-based catalysts have important application value in the degradation of organic pollutants.

[0004] Defect engineering strategies can promote the catalytic activity of catalysts and change the catalytic pathway by regulating the electronic structure of catalysts, thereby improving activation selectivity. 1 O2 or high-valent metal cobalt Co(Ⅳ)=O provides a possibility. Oxygen vacancies (Ov) are the most commonly studied anion vacancies due to their low formation energy, but Ov has a limited effect on the selective activation of PMS. Therefore, researchers have been committed to the development of cationic vacancies. Summary of the invention

[0005] The purpose of the present invention is to provide a cobalt oxide carbon nitride composite material containing cationic vacancies and a preparation method and application thereof, and to use the composite material to activate PMS-type Fenton to degrade organic pollutants, so as to solve the problems existing in the prior art.

[0006] A method for preparing a cobalt oxide carbon nitride composite material containing cationic vacancies comprises the following steps:

[0007] (1) Adding carbon nitride nanosheets and Co(CH3COO)2·4H2O to glycerol and performing a hydrothermal reaction to obtain a glycerol-cobalt / carbon nitride precursor;

[0008] (2) The glycerol-cobalt / carbon nitride precursor obtained in step (1) is calcined at 300-400°C.

[0009] Furthermore, the preparation of the carbon nitride nanosheets includes: placing urea in a muffle furnace and heating it to 550°C, maintaining it for 4-6 hours, cooling it to room temperature, and then placing it in a muffle furnace and heating it to 500°C, and calcining it for 2-4 hours.

[0010] Furthermore, the mass ratio of the carbon nitride nanosheets, Co(CH3COO)2·4H2O and glycerol added is 4:1:380.

[0011] Furthermore, the temperature of the hydrothermal reaction in step (1) is 180-200 °C.

[0012] CoGly has a layered crystal structure consisting of parallel chains of Co−O−Co−O skeletons terminated by −O−C−C(C−OH)−O− groups. During the research process of the present invention, it was found that this layered structure is conducive to the formation of metal defects in the oxide crystals during thermal calcination.

[0013] The cobalt oxide carbon nitride composite material containing cationic vacancies obtained by the preparation method.

[0014] The application of the cobalt oxide carbon nitride composite material containing cationic vacancies is used for the degradation of organic pollutants.

[0015] Furthermore, the organic pollutants include nitrophenol, methylene blue, rhodamine B, atrazine and bisphenol A.

[0016] The present invention selects ultra-thin carbon nitride nanosheets with a large specific surface area as a carrier, uses glycerol cobalt with Co-O-Co-O as a periodic skeleton unit as a precursor, combines it with the carbon nitride nanosheets, and then undergoes thermal oxidation treatment to form Co with cobalt cation vacancies. 3-xO4 / CN composite catalyst. During the preparation process, the strong metal-support interaction can induce the formation of abundant cobalt ion vacancies. In addition, the carbon nitride support can also inhibit the agglomeration of oxide nanoparticles and achieve Co 3-x High dispersion of O4. We applied this catalyst to PMS activation and degradation of organic pollutants. 3-x O4 / CN exhibits good PMS activation and utilization efficiency and p-nitrophenol (PNP) degradation performance (the degradation process does not require light addition). At the same time, the catalyst exhibits good universality and anti-interference properties for different pollutants and different water environments, and has good reusability.

[0017] Compared with the prior art, the present invention has the following advantages:

[0018] (1) Based on the strong metal-support interaction, a Co with abundant cation vacancies was designed and synthesized. 3-x O4 / CN catalyst. Carbon nitride nanosheets as a carrier form a strong metal-carrier interaction with glycerol-cobalt, inducing the formation of abundant cobalt ion vacancies on the surface of cobalt oxide. In addition, the carbon nitride carrier can also inhibit the formation of Co 3-x The agglomeration of O4 inhibits the formation of large particles and realizes small particle size Co 3-x The high dispersion of O4 exposes more metal active sites and further improves the catalytic activity.

[0019] (2) Co with abundant cation vacancies 3-x The O4 / CN catalyst exhibits good PMS activation efficiency (the active center is metal cobalt), and the activation pathway of PMS by the composite material is a non-radical pathway, and the active oxygen species generated are mainly 1 O2 and Co(Ⅳ)=O.

[0020] (3) Co prepared by the present invention 3-x The O4 / CN catalyst showed excellent degradation performance for p-nitrophenol pollutants, and showed good universality and anti-interference ability for different pollutants and different water environments. The catalyst also has good reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 (a) shows Co prepared under different experimental conditions 3-x O4 / CN composites and Co 3-x (b) X-ray diffraction spectrum of O4; (b) thermogravimetric analysis of glycerol-cobalt / carbon nitride precursor.

[0022] Figure 2 (a) Scanning electron microscope image of carbon nitride nanosheets, (b) Co 3-xScanning electron microscope image of O4 / CN-400 composite.

[0023] Figure 3 For Co 3-x Transmission electron microscopy (TEM) images of O4 / CN-400 composites.

[0024] Figure 4 For Co 3-x Electron paramagnetic resonance (EPR) image of O4 / CN composite.

[0025] Figure 5 For Co 3-x PNP catalytic degradation and PMS activation effect test of O4 / CN composite material; including: (a) degradation performance test; (b) PMS consumption.

[0026] Figure 6 For Co 3-x Active species capture diagram and EPR analysis diagram of PMS activated by O4 / CN-400 composite material; (a) Active species capture experimental diagram; (b) 1 EPR test diagram of O2; (c) analysis diagram of methyl phenyl sulfoxide (PMSO) detecting Co(Ⅳ)=O.

[0027] Figure 7 For Co 3-x Anti-interference and stability test of O4 / CN-400 composite materials; (a) Effect of various water environments on Co 3- x Effect of O4 / CN-400 on the degradation of PNP; (b) The degradation effect of the catalyst on different pollutants (20 mg / L); (c) Co 3-x Stability test of O4 / CN-400. DETAILED DESCRIPTION

[0028] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.

[0029] Example 1

[0030] A method for preparing a cobalt oxide carbon nitride composite material containing cationic vacancies comprises the following steps:

[0031] Preparation of ultrathin carbon nitride nanosheets: Place urea in a 250 ml covered crucible, heat it to 550 °C in a muffle furnace at a heating rate of 2.5 °C / min, keep it for 4 h, cool it to room temperature, open the crucible lid, and place it in a muffle furnace and heat it to 500 °C at a heating rate of 5 °C / min. Calcined it for 2 h to obtain ultrathin carbon nitride nanosheets. (2) Co 3-xPreparation of O4 / CN catalyst: 200 mg of carbon nitride and 10-50 mg of cobalt acetate tetrahydrate were added to 19 g of glycerol, stirred to completely dissolve and mix well, and the mixed solution was transferred to a polytetrafluoroethylene reactor, reacted at 180 °C for 2 h, cooled to room temperature, washed with ethanol several times, and the obtained yellow solid was placed in an oven to dry. The above solids were calcined in a muffle furnace at 300 and 400 °C (heating rate: 5 °C / min) for 1 h to obtain Co 3-x O4 / CN composite catalyst, respectively denoted as Co 3-x O4 / CN-300、Co 3-x O4 / CN-400.

[0032] In this example, the amount of carbon nitride and glycerol was fixed, and the amount of cobalt acetate tetrahydrate was changed. The amount of cobalt acetate tetrahydrate was 10, 20, 30, 40, and 50 mg, respectively. It was found that the catalyst performance was best after adding 50 mg of cobalt acetate tetrahydrate.

[0033] Comparative Example 1

[0034] A cobalt oxide containing cation vacancies 3-x The preparation method of O4 catalyst comprises: adding 10-50 mg of cobalt acetate tetrahydrate to 19 g of glycerol, stirring to completely dissolve and fully mix, transferring the mixed solution to a polytetrafluoroethylene reactor, reacting at 180 ° C for 2 h, cooling to room temperature, washing with ethanol several times, and drying the obtained yellow solid in an oven. The above solid is calcined at 300-400 ° C (heating rate: 5 ° C / min) in a muffle furnace for 1 h to obtain Co 3-x O4 catalyst.

[0035] Comparative Example 2

[0036] The amount of cobalt acetate tetrahydrate was changed to 60 mg, and the other steps and conditions were the same as those in Example 1. The obtained catalyst was recorded as Co 3-x O4 / CN-60 mg.

[0037] When 60 mg or more of cobalt acetate tetrahydrate is added, the metal acts as a catalyst during the calcination process, which catalyzes the decomposition of carbon nitride. It is found that the carbon nitride decomposes faster due to the increase in metal content. Therefore, the optimal amount of cobalt acetate tetrahydrate added is 50 mg.

[0038] Comparative Example 3

[0039] The obtained yellow solid was dried in an oven and then calcined in a muffle furnace at 450 and 500 °C (heating rate: 5 °C / min) for 1 h, respectively. The other steps and conditions were the same as those in Example 1.

[0040] The experiment found that when the calcination temperature rises to above 450℃, the presence of metal accelerates the decomposition of carbon nitride. Above 400℃, carbon nitride is completely decomposed and no composite catalyst is obtained. Therefore, the maximum calcination temperature can only reach 400℃.

[0041] Comparative Example 4

[0042] Add 2.5 g urea and 50 mg cobalt acetate tetrahydrate to 19 g glycerol, stir to completely dissolve and mix well, transfer the mixed solution to a polytetrafluoroethylene reactor, react at 180 °C for 2 h, cool to room temperature, and then centrifuge and wash with ethanol.

[0043] It was found that no solid precipitate was generated during the centrifugation process, which may be because the addition of urea hindered the formation of glycerol-cobalt structure, and ultimately no catalyst was obtained.

[0044] Comparative Example 5

[0045] 5 g of melamine was placed in a 50 ml covered crucible, and the temperature was raised to 520 °C in a muffle furnace at a heating rate of 5 °C / min and maintained for 4 h to obtain bulk carbon nitride. The ultrathin carbon nitride nanosheets used in Example 1 were replaced with bulk carbon nitride obtained under the above conditions, and the other steps and conditions were the same as in Example 1. The obtained catalyst was recorded as Co 3-x O4 / CN-h.

[0046] The experiment found that Co obtained from carbon nitride prepared from melamine 3-x The degradation performance of O4 / CN-h composites is significantly worse than that of CoO4 / CN-h composites prepared from ultrathin carbon nitride nanosheets using urea as raw material. 3-x O4 / CN composite catalyst. The ultra-thin carbon nitride nanosheets prepared using urea as raw material have a large specific surface area and better performance.

[0047] Experimental data

[0048] 1. XRD data analysis

[0049] The prepared Co 3-x O4 / CN-400、Co 3-x O4 catalyst was subjected to X-ray diffraction analysis, such as Figure 1 As shown in (a), Co 3-x The main diffraction peak of O4 is attributed to the characteristic peak of Co3O4 (PDF#76-1802). 3-x The only diffraction peak observed for O4 / CN-400 is at 13.1 o and 27.8 oThe two peaks at 0.04 and 0.13 are attributed to the (100) and (002) crystal planes of carbon nitride, indicating that Co 3-x The loading of O4 did not destroy the structure of carbon nitride. And there was no Co3O4 characteristic peak, suggesting that Co 3-x The content of O4 is low (ICP-AES measured the cobalt content to be 6wt%), the particle size is small and highly dispersed. 3-x O4 / CN-400 comparison, when the amount of cobalt acetate added is 60 mg, the catalyst Co 3-x The diffraction peak of carbon nitride (27.8 o ) was significantly weakened, and the diffraction peak of Co3O4 appeared, indicating that the increase of metal content will catalyze the decomposition of carbon nitride. When the calcination temperature is increased to 450 o C, the diffraction peak of carbon nitride (13.1 o and 27.8 o ) disappears, and only the diffraction peak of Co3O4 appears, indicating that the increase in calcination temperature will lead to the complete decomposition of carbon nitride. Figure 1 As shown in (b), the thermogravimetric analysis shows that the glycerol-cobalt / carbon nitride precursor o C, a significant weight loss was observed, further confirming that carbon nitride o C will decompose rapidly. Therefore, the calcination temperature should be above 400 o C, the glycerol-cobalt / carbon nitride precursor will undergo thermal decomposition and no catalyst will be obtained.

[0050] 2. SEM data analysis

[0051] The ultrathin carbon nitride nanosheets and Co 3-x The O4 / CN-400 catalyst was subjected to scanning electron microscopy analysis. Figure 2 As shown. It can be observed that Co 3-x O4 / CN-400 shows a nanosheet structure similar to carbon nitride and has no obvious Co 3-x O4 particles were observed, indicating that Co 3-x The particle size of O4 nanoparticles is small and highly dispersed, which is consistent with the XRD conclusion.

[0052] 3. TEM data analysis

[0053] like Figure 3 As shown in Figure 1, transmission electron microscopy analysis shows that the particle size of the metal oxide is about 2-3 nm and is highly dispersed on the carbon nitride support. High-resolution TEM shows that the lattice fringe spacing is 0.24 nm, which belongs to the (311) crystal plane of Co3O4, indicating that the cobalt oxide exists in the form of Co3O4 and has no obvious agglomeration.

[0054] 4. Electron paramagnetic resonance analysis

[0055] The prepared Co 3-x The O4 / CN-400 catalyst was subjected to electron paramagnetic resonance analysis, such as Figure 4 As shown in Figure 2, the composite material has a symmetric signal at g = 2.005, confirming the existence of cobalt vacancies. 3-x Compared with O4, Co 3-x The EPR signal intensity of O4 / CN-400 increased significantly, proving that after the introduction of carbon nitride, the strong metal oxide-support interaction can significantly increase the concentration of cationic vacancies. At the same time, appropriately increasing the calcination temperature (such as 300 ℃ to 400 ℃) is also conducive to the generation of cobalt vacancies.

[0056] 5. Co 3-x Evaluation of the performance of O4 / CN catalyst for the Fenton-like degradation of PNP by PMS

[0057] Weigh 10 mg Co 3-x The O4 / CN catalyst was placed in a 150 mL beaker, and PNP solution (30 mL, 20 mg / L) was added and stirred for 10 min to achieve adsorption-desorption equilibrium between the catalyst and the PNP pollutant. Then, a certain amount of PMS was added to initiate the reaction. During the reaction, 2.5 mL of the suspension was taken out at a given time interval, the catalyst was filtered to remove, and 0.5 mL of methanol solution was immediately added to quench the reaction. The absorbance was measured at 400 nm using a UV-visible spectrophotometer to analyze the residual concentration of PNP. The experimental results are shown in Figure 2. Figure 5 As shown in (a), the comparative experiment found that Co 3-x O4 has basically no ability to activate PMS, and PMS alone can basically not degrade pollutants. 3-x Co obtained after O4 coupling 3-x The performance of the O4 / CN-400 catalyst was greatly improved, and the degradation efficiency of PNP reached 98.7% after 15 min of reaction (degradation rate constant k = 0.23 min -1 ). Under the same conditions, Co 3-x O4 / CN-h only degraded 19.8% in 30 min, while Co 3-x O4 / CN-300 can only reach 98.7% PNP degradation rate after 30 min (degradation rate constant k = 0.12 min -1 ), Co 3-x The degradation rate constant of O4 / CN-400 is Co 3-x O4 / CN-300. This phenomenon indicates that Co with high concentration of cobalt ion vacancies 3-xO4 / CN-400 can significantly improve the degradation efficiency of the catalyst. Figure 5 (b) shows the PMS consumption under different catalytic systems, among which Co 3-x O4 / CN-400 has the highest activation efficiency for PMS, which further illustrates that the presence of cationic vacancies can effectively promote the activation of PMS.

[0058] 6. Active species capture experiments and EPR tests

[0059] like Figure 6 As shown in (a), methanol (MA), tert-butyl alcohol (TBA), methyl phenyl sulfoxide (PMSO) and histidine (L-his) were used to capture SO4 ·- and ·OH, ·OH, Co(Ⅳ)=O and 1 O2, and the other steps are the same as the above degradation experimental steps. Figure 6 Middle (b): 2, 2, 6, 6-tetramethyl-4-piperidinol (TEMP) 1 The O2 capture agent detects the EPR signal. Figure 6 By comparison in (a), it is found that the main factors are Co(Ⅳ)=O and 1 O2. Figure 6 In (b), the EPR test confirmed the existence of the catalytic system 1 O2, Figure 6 In (c), the production of Co(Ⅳ)=O was further confirmed by the consumption of PMSO and the generation of PMSO2.

[0060] 7. Anti-interference and stability test

[0061] The prepared Co 3-x O4 / CN-400 catalyst was tested for anti-interference and stability, such as Figure 7 As shown in (a), the catalyst still maintains excellent degradation performance in different water environments, indicating that the system has good anti-interference ability. Figure 7 As shown in (b), in addition to PNP, the catalyst can also effectively oxidize various pollutants, such as methylene blue, rhodamine B, atrazine and bisphenol A. The above pollutants can be effectively degraded within 5 minutes, and the degradation rate is as high as 100%, which verifies that the catalyst has excellent degradation effects on various pollutants. Figure 7 As shown in (c), the degradation rate of the catalyst still reaches 89.6% after five cycles, proving that the catalyst has good reusability.

Claims

1. A method for preparing a cobalt oxide carbon nitride composite material containing cationic vacancies, characterized in that: The following steps are involved: (1) Adding carbon nitride nanosheets and Co(CH3COO)2·4H2O to glycerol and performing a hydrothermal reaction to obtain a glycerol-cobalt / carbon nitride precursor; (2) calcining the glycerol-cobalt / carbon nitride precursor obtained in step (1) at 300-400°C for 1h; The mass ratio of the carbon nitride nanosheets, Co(CH3COO)2·4H2O and glycerol added is 4:1:380; The preparation of the carbon nitride nanosheets comprises: placing urea in a muffle furnace, heating it to 550°C, maintaining it for 4-6 hours, cooling it to room temperature, and then placing it in a muffle furnace, heating it to 500°C, and calcining it for 2-4 hours.

2. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 180-200°C.

3. A cobalt oxide carbon nitride composite material containing cationic vacancies obtained according to the preparation method of claim 1 or 2.

4. The use of the cobalt oxide carbon nitride composite material containing cationic vacancies according to claim 3, characterized in that: Used for the degradation of organic pollutants.

5. The application according to claim 4, characterized in that: The organic pollutants include nitrophenol, methylene blue, rhodamine B, atrazine and bisphenol A.

Citation Information

Patent Citations

  • Nanometer Co 3O4 with cobalt defects and preparation method thereof, and application thereof in oxygen production through electro-catalysis water decomposition

    CN106315691A

  • Preparation method and application of oxygen vacancy-rich cobaltosic oxide quantum dot composite catalyst loaded on carbon nitride nanosheet

    CN116550365A